Financial frictions in Mexico: Evidence from the credit spread and its components - Mauricio Carabarín Aguirre; Carlos D. Peláez Gómez (Banco de México, 2021)
We investigate the relationship between financial market frictions and economic activity in Mexico by constructing and decomposing a credit spread index from bonds issued by non-financial corporations in domestic markets, following Gilchrist and Zakrajsek (2012). We show that the credit spread is significantly informative about the evolution of economic activity and financial aggregates in Mexico. Moreover, the excess bond premium (EBP), which tracks the relationship between firms' default risk and their credit spread, is found to be the main driver of this relationship. We show evidence that negative shocks on financial conditions, identified as a sudden increase of EBP, prompt a contraction in economic activity and credit aggregates. Finally, we find evidence of non-linear effects on the responses of economic activity in response to the shock.
Keywords: E32; E44; 330; Credit spread; economic activity; credit aggregates